MERCADO RELIGIOSO E NEOPENTECOSTALISMO: Uma análise do crescimento da Igreja Evangélica Nova Aliança em Imperatriz- MA - SILVA, Washington de Araújo (2024)
This research analyzes the growth of the Igreja Evangélica Nova Aliança (New Covenant Evangelical Church) in Imperatriz, state of Maranhão, Brazil. The interest in this research originated from the observation that in the last twenty years, the evangelical landscape of this city has undergone significant changes due to the structuring of neo-Pentecostal churches into cells, which began their activities between the late 1990s and early 2000s. The Igreja Evangélica Nova Aliança, founded in July 2005, has been one of the churches responsible for modifying this scenario through the implementation of changes in the scope of religious practices and offerings, thus contributing to intensifying competition in the local religious market. The main question that guides this research is: how does the growth of the Igreja Evangélica Nova Aliança occur in the city of Imperatriz? Based on this question, during the reflection, it is argued that the growth of this religious agency occurs in the midst of a competition system in the national and, above all, local evangelical field, with direct impacts on the organizational management model and religious work of this church. The development of the reasoning is theoretically based on the concept of religious rationalization by Weber (2000; 2004) and Bourdieu (2007); and on the theory of the religious market developed by Berger (1984; 2017); Stark (2004); Stark and Bainbridge (2008) and Stark and Iannaccone (1994). The methodology used was qualitative in nature. Thus, we did in-person observation to visualize the practices and representations of the institution in loco. Also, to obtain more information, we used websites, social media profiles, books and teaching materials of courses offered by the church, in addition we conducted semi-structured interviews. The results showed that the growth of this institution occurs due to the existence of a religious demand that it manages to meet through the implementation of a management and religious work model that allows it to offer religious content and products according to the needs of the consumers. Finally, through this research, we sought to contribute to the understanding of the processes that involve the reproduction of the religious phenomenon and the restructuring of the neopentecostal evangelical market in the city of Imperatriz - MA.